2021
DOI: 10.1158/1535-7163.mct-20-0014
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human, Phase 1 Dose-Escalation Study of Biparatopic Anti-HER2 Antibody–Drug Conjugate MEDI4276 in Patients with HER2-positive Advanced Breast or Gastric Cancer

Abstract: MEDI4276 is a biparatopic tetravalent antibody targeting 2 nonoverlapping epitopes in subdomains 2 and 4 of the HER2 ecto-domain, with site-specific conjugation to a tubulysinbased microtubule inhibitor payload. MEDI4276 demonstrates enhanced cellular internalization and cytolysis of HER2+ tumor cells in vitro. This was a first-in-human, dose-escalation clinical trial in patients with HER2+ advanced or metastatic breast cancer (BC) or gastric cancer.MEDI4276 doses escalated from 0.05-0.9 mg/kg (60-90-minute IV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Several bi-paratopic antibodies have been reported in different tumor models [27-30]. In a breast cancer model, a bi-paratopic antibody shows enhanced avidity and cross linking activity to promote HER2 clustering and lysosomal degradation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several bi-paratopic antibodies have been reported in different tumor models [27-30]. In a breast cancer model, a bi-paratopic antibody shows enhanced avidity and cross linking activity to promote HER2 clustering and lysosomal degradation [27].…”
Section: Discussionmentioning
confidence: 99%
“…These results were also re-capitulated in in vivo models. The experimental success of this agent, now termed MEDI4276, has led to its deployment in a phase I clinical trial concluded in August 2021 [40]. ZW49, is a similar HER2-targeting biparatopic ADC.…”
Section: Multispecific Adcsmentioning
confidence: 99%
“…Unfortunately, in the phase Ⅱ dose-escalation and expansion study ( identifier: NCT02576548), even though MEDI4276 demonstrated obvious clinical activity, it still showed unbearable toxicity when the dose was higher than 0.3 mg/kg. Common toxicities included nausea, fatigue and vomiting [ 65 ]. The clinical development of MEDI4276 was severely delayed due to high incidences of drug-related adverse reactions, and it was therefore halted.…”
Section: Therapymentioning
confidence: 99%